A Randomized, Prospective, Observer-Masked Study Comparing Dropless Treatment Regimen Using Intracanalicular Dexamethasone Insert, Intracameral Ketorolac, and Intracameral Moxifloxacin versus Conventional Topical Therapy to Control Postoperative Pain and Inflammation in Cataract Surgery - Donnenfeld ED; Hovanesian JA; Malik AG; Wong A (Clinical Ophthalmology, 2023)
Eric D Donnenfeld,1 John A Hovanesian,2 Aysha G Malik,1 Aidan Wong1 1Ophthalmic Consultants of Long Island, New York, NY, USA; 2Harvard Eye Associates, Laguna Hills, CA, USACorrespondence: Eric D Donnenfeld, Ophthalmic Consultants of Long Island (OCLI), 711 Stewart Avenue, Suite 160, Garden City, New York, NY, 11530, USA, Tel +1 516-500-4200, Fax +1 516-742-0017, Email ericdonnenfeld@gmail.comPurpose: To evaluate clinical efficacy and patient preference for a dropless treatment regimen compared to conventional topical therapy in patients undergoing cataract surgery.Patients and Methods: In this prospective, contralateral eye study, patients with bilateral cataract were randomized to receive either intracanalicular dexamethasone insert, intracameral phenylephrine 1%/ketorolac 0.3%, and intracameral moxifloxacin (50 μg) (study group) or topical moxifloxacin 0.5%, ketorolac 0.5%, and prednisolone acetate 1.0% QID (control group). The second eye underwent cataract surgery 2 weeks later and was treated with the opposite treatment. All patients were evaluated at Days 1, 7, 14, 28, and 3 months. The primary outcome measure was postoperative ocular pain. Secondary outcomes included summed ocular inflammation score (SOIS; the sum of the mean anterior chamber cells and anterior flare score), the patient preference for medication protocol between the two eyes, and patient out-of-pocket cost of medications. Safety outcome measures included CDVA, intraocular pressure, central retinal thickness (CRT), and the incidence of reported AEs.Results: The proportion of patients with no pain was similar in both groups at all postoperative visits (p> 0.05). No statistically significant difference in SOIS score was observed between the two groups at any visit. A strong majority of the patients (94.7%) preferred the study eye’s dropless regimen over the control eye’s conventional topical therapy regimen. No statistically significant difference in mean intraocular pressure (IOP) was observed at any postoperative visit, except at Week 1. The mean CDVA was also similar in both groups at all postoperative visits (p> 0.05). The postoperative mean CRT was comparable between the two groups.Conclusion: A dropless treatment regimen is as effective as topical eyedrop administration. A higher proportion of patients who underwent bilateral cataract surgery preferred the dropless treatment regimen over the patient-administered eye drop regimen.Keywords: dropless cataract surgery, intracanalicular dexamethasone insert, dropless vs topical eyedrop administration, sustained-release steroid delivery, drop-free treatment regimen